2020
DOI: 10.3390/ijerph17082699
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Non-optimum Ambient Temperature on Years of Life Lost: A Multi-county Observational Study in Hunan, China

Abstract: The ambient temperature–health relationship is of growing interest as the climate changes. Previous studies have examined the association between ambient temperature and mortality or morbidity, however, there is little literature available on the ambient temperature effects on year of life lost (YLL). Thus, we aimed to quantify the YLL attributable to non-optimum ambient temperature. We obtained data from 1 January 2013 to 31 December 2017 of 70 counties in Hunan, China. In order to combine the effects of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Subgroup analysis showed that the young and middle‐aged group (18–64 years) may have a higher risk of CRS attributable to ambient temperatures than the elderly. This age group difference in susceptibility was consistent with some studies 11,39 and contrary to others 40,41 . Young and middle‐aged people were more likely to be exposed to extreme temperatures while working or exercising outdoors, but they also changed their activity habits because of the uncomfortable temperatures.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Subgroup analysis showed that the young and middle‐aged group (18–64 years) may have a higher risk of CRS attributable to ambient temperatures than the elderly. This age group difference in susceptibility was consistent with some studies 11,39 and contrary to others 40,41 . Young and middle‐aged people were more likely to be exposed to extreme temperatures while working or exercising outdoors, but they also changed their activity habits because of the uncomfortable temperatures.…”
Section: Discussionsupporting
confidence: 91%
“…This age group difference in susceptibility was consistent with some studies 11,39 and contrary to others. 40,41 Young and middle-aged people were more likely to be exposed to extreme temperatures while working or exercising outdoors, but they also changed their activity habits because of the uncomfortable temperatures. More research is needed to determine the exact differences in temperature sensitivity between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusion-transmissible infections frequency rate was estimated according to the formula: 15 TTI incidence=(confirmed cases)/(total number of annual donors) x 100,000…”
Section: Discussionmentioning
confidence: 99%
“…Then, we computed the individual YLL by matching the age and sex of each death to the 100-year life table. The life table was presented in a previous article (Lv et al 2020 ). For each location, daily total YLLs of CVD were calculated by summing all individual YLLs on the same day.…”
Section: Methodsmentioning
confidence: 99%